Tecendo: narrativas de vida como potencia para fazer arte no contexto escolar - Simone Torres de Lima Bernardino (2023)
This research stems from my practice and position as na artist/teacher/researcher, when I bring my experiences and visual productions, using embroidery as a material to establish a connection between the artist-self and the teacher-researcher-self. By incorporating theorical aspects and presenting the poetry that emerges through my path and the children in public schools, I aim to elucidate how art education takes place in this setting and how I brought embroidery into the classroom, as well as how the process of embroidery unfolded for children and teenagers. Drawing on comtemporary references in embroidery, such as Rosana Paulino, Arthur Bispo do Rosário, Edith Derdyk, and that, in some way, became part of the narrative and production of these children. As a subject, I am engaged in na investigation that is umbued with my practice, where my research takes place within the realm of the artist-teacher-researcher. The children give us clues about how urgente it still is to look at art education within schools, and with them, I navigate through this next using the a/r/tographic research method, na “educational research methodology based on art”, by Irwin (2003); I also follow the path of (auto)biographical research by Delory-Momberger (2016). Drawing on these references, I seek to investigate art teaching/learning thar starts from my production, in a contemporary perspective, based on the experiences and lives of students, using embroidery as a thread of connection. I in a place of childhood that I arrived at embroidery.